Changing dynamics of the U.S.–Nepal policy: An analysis through the lens of hegemonic stability theory - Lamichhane, Dron Prasad (Nepal Public Policy Review, 2025)
This study examines the evolving dynamics of U.S.–Nepal relations through the lens of Hegemonic Stability Theory (HST), focusing on the period from establishment of diplomatic ties to Biden administration. The objectives are to analyze U.S.–Nepal foreign policy initiatives, assess Nepal’s positioning within these policies, and apply HST to understand the interactions. Utilizing a descriptive-analytical approach to collect, descibe and analyse relevant data from academic sources and grey literature, the study highlights Nepal’s strategic importance amid shifting global and regional power dynamics. Findings indicate that U.S.–Nepal relations have been shaped by the U.S. goal of maintaining a balance between China and India, particularly during the Cold War. U.S. policy emphasized supporting Nepal’s sovereignty and democratic development in coordination with India to counter communist influence. Following the Cold War, U.S. engagement with Nepal increased, driven by regional dynamics and concerns, including the Maoist insurgency and War on Terror. As global power structures shifted from unipolarity to multipolarity, U.S. policy towards Nepal has remained unchanged in terms of development assistance through the USAID program and the recent Millennium Challenge Corporation (MCC) agreement. Although the U.S. has always consistently maintained that MCC is a bilateral development program, it has frequently been characterized in Nepal’s public discourse as a instrument of the Indo-Pacific Strategy. Despite deepening engagement, Nepal remains concerned that Indian perspectives are shaping U.S. policies towards Nepal. The study concludes by providing critical insights into U.S.–Nepal relations, suggesting that Nepal needs to redefine its foreign policy to engage more independently with the U.S., while balancing regional pressures and strengthening its institutional capacity to counter misinformation and check foreign influence over public discourse.